PENGARUH PENAMBAHAN SERAT AMPAS TEBU GILING MANUAL DAN GILING PABRIK TERHADAP KUALITAS ETERNIT - Darmono1) Sukarman2) (Universitas Negeri Yogyakarta, 2011)
This research study is determine the influence of the addition of bagasse fibers based on quality of plasterboard, which include: the absorption of water, the density of water, the ability of nailed, and flexural strength. This research was carried out in the Laboratory of building materials of YSU and Laboratory Of Structures GMU. The specimens for each composition consist of five pieces. The research method using experiment approach, the data then analyzed with compare the test result and SII.0016-72. The mix of bagasse fibers were 1sp:3kp:1st, 1sp:3kp:2st, 1sp:3kp:3st, 1sp:3kp:4st, and 1sp:3kp:5st respectively. Water absorption test results using the milling of bagasse fibers manual, the weight of content, and flexural strength for the composition 1sp:3kp:1st, 1sp:3kp:2st, 1sp:3kp:3st, 1sp:3kp:4st, and 1sp:3kp:5st the result were 21.95%, 18.68%, 21.80%,24.87%, 23.96%; 2.24gr/cm3, 2.15gr/cm3, 2.16gr/cm3, 1.18gr/cm3, 1.8gr/cm3 and 45.65kg/m², 47.34kg/m2, 91.73kg/m2, 26.74kg/m2 and 36.4kg/m2, respectively. The water density and visual test results for composition I, II, and III are good, whereas for composition III and IV occurring droplets. The capability test nailed does not occur crack on all composition. The water absorption, weight of content and flexural strength test results using the milling of bagasse fibers for mixed composition 1sp:3kp:2st, 1sp:3kp:3st, and 1sp:3kp:4st were 8.35%, 11.35%, 15.44%; 2.92gr/cm3, 2.73 gr/cm3, 2.41 gr/cm3 and 51.37kg/m2, 101.66kg/m2 and 73.93kg/m2 respectively. The density of water with co mposition 1sp:3kp: 2st, and 1sp: 3kp: 3st does not occur while the droplets to composition 1sp: 3kp: 4st. The capability test nailed does not occur crack on all composition, it is of the best qualified based on SII. 0016-72 is 1sp: 3kp: 3st with bagasse fiber.